In vivo calcium imaging visualizes peripheral neuron sensitization in a surgical mouse model of osteoarthritis - Miller, Rachel E. (Arthritis Rheumatol, 2017)
OBJECTIVE: The purpose of this study was to develop a method for analyzing sensory neuron responses to mechanical stimuli in vivo, and to evaluate whether these neuronal responses change after destabilization of the medial meniscus (DMM). METHODS: DMM or sham surgery was performed in 10-week old male C57BL/6 wild-type or Pirt-GCaMP3(+/−) mice. All experiments were performed eight weeks after surgery. Knee and hind paw hyperalgesia were assessed in wild-type mice. The retrograde label DiI was injected into the ipsilateral knee to quantify the number of knee-innervating neurons in the L4 dorsal root ganglion (DRG) in wild-type mice. In vivo calcium imaging was performed on the ipsilateral L4 DRG of Pirt-GCaMP3(+/−) mice as mechanical stimuli (paw pinch, knee pinch, knee twist) were applied to the ipsilateral hind limb. RESULTS: Eight weeks after surgery, DMM mice had more hyperalgesia in the knee and hind paw compared to sham mice. Intra-articular injection of DiI labeled similar numbers of neurons in the L4 DRG of sham and DMM mice. Increased numbers of sensory neurons responded to all three mechanical stimuli in DMM mice, as assessed by in vivo calcium imaging. The majority of responses in sham and DMM mice were in small-to-medium-sized neurons, consistent with the size of nociceptors. The magnitude of responses was similar between sham and DMM mice. CONCLUSIONS: We demonstrated that increased numbers of small-to-medium sized DRG neurons respond to mechanical stimuli 8 weeks after DMM surgery, suggesting that nociceptors have become sensitized by lowering the response threshold.